Characterization of focal liver lesions: Use of mangafodipir trisodium (MnDPDP)-enhanced MR images - Aydın KARABACAKOĞLU; Yüksel ADIGÜZEL; Serdar KARAKÖSE; Ertuğrul KAYAÇETİN and Rahime HAYKIR (Turkish Journal of Gastroenterology, 2019)
-